Design and development of porous CoCrFeNiMn high entropy alloy Cantor alloy with outstanding electrochemical properties - Abid, Talha (2024)
CoCrFeNiMn high entropy alloys are among the most well-studied high entropy alloys that exhibit reasonable strength and outstanding ductility. In the present study, porous CoCrFeNiMn foams have been developed by the addition of copper in the base high entropy alloy by arc melting followed by its removal through an electrochemical dealloying process. Microstructure characterization of the as-cast samples confirmed limited solubility of copper in the matrix while the majority of the copper was found to segregate to interdendritic areas. Removal of copper from the interdendritic areas was successfully carried out by an electrochemical dealloying process which resulted in the development of foams with interconnected porosity. CoCrFeNiMn foams with different levels of porosities were successfully developed by varying the amount of added copper in the base HEA and its removal by a dealloying process. The electrochemical performance of the developed foams was assessed by cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), and electrochemical impedance spectroscopy (EIS). One of the developed foams was found to exhibit an areal capacitance of 1.56 F cm 2 at 2 mA cm 2 which is more than 2x times higher than the value reported for recently developed porous AlCoCrFeNi high entropy foam. Developed foam, besides showing excellent values of areal capacitance, demonstrated capacitance retention of 114.6% after 5000 cycles at 8 mA cm 2. The excellent electrochemical performance of the developed high entropy foams exhibits their potential to be used as electrode materials for supercapacitor applications and was attributed to the insertion of interconnected porosity in the base HEA.